Peningkatan Sistem Imun Keluarga Di Era Pandemi Covid-19 - Sri Nabawiyati Nurul Makiyah; Nurvita Risdiana (Poltekkes Kemenkes Surakarta, 2021)
Background: The Covid-19 pandemic has triggered public awareness to stay at home, so that community gathering activities are canceled, including routine community gymnastics activities. The aim of its community service activity is to increase public awareness of the Salakan hamlet regarding health protocols by increasing the family's immune system and physical activity during the Covid-19 pandemic for women in the Salakan, Trihanggo, Gamping, Sleman. Methods: this community services activity used lectures on improving the family's immune system and appropriate physical activity in the era of the Covid-19 pandemic. The lectures and discussions both offline and online course. It is done offline at the residents' meeting building on March 1, 2021 with 20 Health Cadres whose members are the same as the Salakan women's gymnastics board. MS Teams meeting online on Sunday, February 7, 2021. Evaluation is done by measuring the level of knowledge of participants about the immune system and the level of knowledge about physical activity is done through posttest with google form. Results: this community service activity showed that the participants were very enthusiastic and there was a warm discussion about the topic given. Post-test results showed that the level of knowledge of participants about the immune system was 80.00 ± 10.34 (very good) and the level of knowledge about physical activity was 76.25 ± 15.00 (good). Conclusion: the women of the Gymnastics group after being given socialization about the immune system and physical activity experienced an increase in knowledge about how to improve the immune system and what physical activities were good to do during the Covid-19 pandemic.